Cause for event: not-for-profit marketing through participant sports events - Taylor, Ruth; Shanka, Tekle (Gatehouse Design and Print Consultancy RGU, 2008)
The purpose of this paper was to investigate the motivations of participants attending a sportsevent organised by a not-for-profit organisation as a major source of revenue generation. Aquestionnaire was placed on the website for participants to complete, resulting in a response of N= 218. Overall, there was an evenly distributed age range of respondents, 55% being male. Twothirds of the respondents had participated in the event previously, with most taking part in theevent with a partner or friends. The findings indicate that participants placed higher motivationvalue on personal benefits such as to challenge themselves, to have fun, to get fit and to improvetheir athletic ability. It also found that lower motivation was scored for the philanthropic benefitsfor the charity staging the event shown by the lower score attributed to the motivator of raisingmoney for charity. Statistically significant differences were found in motivation between gender,with females achieving significantly higher scores on the motivators of having fun, wanting toprove to themselves that they could do it and raising money for charity. These findings havesignificance for not-for-profit marketing strategies when segmenting those attending not-forprofitrevenue generating events.